IN SITU MEASUREMENT OF THE SOIL MOISTURE CONTENT PROFILE AT A DECOMPOSED GRANITE CUT-SLOPE - Adrin Tohari; Makoto Nishigaki (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2010)
ABSTRACT Two selected sites at a decomposed granite cut-slope were instrumented with a rain gauge and a series of ThetaProbes installed at depths up to 90 cm from the slope surface. The objective of this study was to evaluate the significance of antecedent soil moisture conditions in controlling the hydrologic responses of the soils at each site. The antecedent moisture content of the soil in Site #1, in general, increases with depth. The response of the soil to saturation process is more or less confined to the shallow depth. On the other hand, the measurement data of the soil in Site #2 showed that the near surface soil exhibits higher antecedent moisture condition than the deeper soil. The ingress of the wetting front could reach more than 90 cm depth during long period of rainfall. Thus, these results suggest that the hydrological response of the soils is spatially variable and is influenced by the antecedent soil moisture conditions within the soil profile. The presence of soil layers, the distribution of macro cracks within the soil profile, and additional lateral source of moisture may also have significant influences on soil response to saturation process.